Where are our Doctoral candidates coming from and why. Final report. - Kiley, Margaret (Australian Learning and Teaching Council (ALTC), 2011)
The Department of Innovation, Industry, Science and Research's 2010 paper on Meeting Australia's research workforce needs identified three national challenges: the provision of sufficient higher degree research graduates to meet workforce demands, the standards and quality of an Australian degree and graduate, and suitable and sufficient career pathways for graduates. This small-scale pilot study aimed to provide some answers to questions such as : How and why do students end up enrolling in a doctorate, What is the exit point and qualification if they leave the program without completing, and where do they go after their program. It outlined a more extensive study so that a clearer understanding of the pathways in, through, out of, and from doctoral programs in Australia is gained. The value of such a study is that the findings will help to position Australian higher education to be forward looking with regard to research education.